Responses of ichthyoplankton assemblages to the recent marine heatwave and previous climate fluctuations in several Northeast Pacific marine ecosystems. (12th December 2020) - Nielsen, Jens M.; Rogers, Lauren A.; Brodeur, Richard D.; Thompson, Andrew R.; Auth, Toby D.; Deary, Alison L.; Duffy‐Anderson, Janet T.; Galbraith, Moira; Koslow, J. Anthony; Perry, R. Ian
Abstract: The effects of climate warming on ecosystem dynamics are widespread throughout the world's oceans. In the Northeast Pacific, large‐scale climate patterns such as the El Niño/Southern Oscillation and Pacific Decadal Oscillation, and recently unprecedented warm ocean conditions from 2014 to 2016, referred to as a marine heatwave (MHW), resulted in large‐scale ecosystem changes. Larval fishes quickly respond to environmental variability and are sensitive indicators of ecosystem change. Categorizing ichthyoplankton dynamics across marine ecosystem in the Northeast Pacific can help elucidate the magnitude of assemblage shifts, and whether responses are synchronous or alternatively governed by local responses to regional oceanographic conditions. We analyzed time‐series data of ichthyoplankton abundances from four ecoregions in the Northeast Pacific ranging from subarctic to subtropical: the Gulf of Alaska (1981–2017), British Columbia (2001–2017), Oregon (1998–2017), and the southern California Current (1981–2017). We assessed the impact of the recent (2014–2016) MHW and how ichthyoplankton assemblages responded to past major climate perturbations since 1981 in these ecosystems. Our results indicate that the MHW caused widespread changes in the ichthyoplankton fauna along the coast of the Northeast Pacific Ocean, but impacts differed between marine ecosystems. For example, abundances for most dominant taxa were at all‐time lows since the beginning of sampling in the Gulf of Alaska and British Columbia, while in Oregon and the southern California Current species richness increased as did abundances of species associated with warmer waters. Lastly, species associated with cold waters also increased in abundances close to shore in southern California during the MHW, a pattern that was distinctly different from previous El Niño events. We also found several large‐scale, synchronized ichthyoplankton assemblage composition shifts during past major climate events. Current climate projections suggest that MHWs will become more intense and thus our findings can help project future changes in larval dynamics, allowing for improved ecosystem management decisions. Abstract : Unprecedented warm ocean conditions from 2014 to 2016, also referred to as a marine heatwave (MHW) caused extensive changes to the physical and biological oceanographic conditions in the Northeast Pacific ocean. Using time‐series data of ichthyoplankton abundances from four adjacent but biogeographically‐different ecoregions ranging from subarctic to subtropical: the Gulf of Alaska, British Columbia, and the northern and southern California Current, we show that the MHW caused widespread changes in the ichthyoplankton fauna in Northeast Pacific Ocean but that responses were clearly different between ecosystems.